Aggressive Supratentorial Ependymoma, Fusion-Positive with Extracranial Metastasis: A Case Report - Seong-Ik Kim (Journal of Pathology and Translational Medicine, 2017)
Ependymoma is the third most common pediatric primary brain tumor. Ependymomas are categorized according to their locations and genetic abnormalities, and these two parameters are important prognostic factors for patient outcome. For supratentorial (ST) ependymomas, RELA fusion-positive ependymomas show a more aggressive behavior than YAP1 fusion-positive ependymomas. Extracranial metastases of intra-axial neuroepithelial tumors are extremely rare. In this paper, we report a case of aggressive anaplastic ependymoma arising in the right frontoparietal lobe, which had genetically 1q25 gain, CDKN2A homozygous deletion, and L1CAM overexpression. The patient was a 10-year-old boy who underwent four times of tumor removal and seven times of gamma knife surgery. Metastatic loci were scalp and temporalis muscle overlying primary operation site, lung, liver, buttock, bone, and mediastinal lymph nodes. He had the malignancy for 10 years and died. This tumor is a representative case of RELA fusion-positive ST ependymoma, showing aggressive behavior.